2016
DOI: 10.1097/hcr.0000000000000166
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Utilization of Cardiac Rehabilitation Among Patients With Ischemic Heart Disease in the Veterans Health Administration

Abstract: Our findings suggest that addressing access issues and educating and activating providers on CR may increase utilization of CR programs. Targeting these specific factors may improve utilization of CR programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Transportation and travel issues can be of particular burden to older patients who are less able to drive long distances necessary to participate in traditional facility-based programs. [87][88][89] A burgeoning concept of home-based and hybrid CR programs aims to bridge a gap between patients willing and able to participate in facility-based programs and who are limited by logistics or other impediments. However, they have yet to be well-studied in patients with HF and important questions and concerns remain regarding whether CR is safe and effective at home for older patients with HF, and whether it will be reimbursed.…”
Section: Challengesmentioning
confidence: 99%
“…Transportation and travel issues can be of particular burden to older patients who are less able to drive long distances necessary to participate in traditional facility-based programs. [87][88][89] A burgeoning concept of home-based and hybrid CR programs aims to bridge a gap between patients willing and able to participate in facility-based programs and who are limited by logistics or other impediments. However, they have yet to be well-studied in patients with HF and important questions and concerns remain regarding whether CR is safe and effective at home for older patients with HF, and whether it will be reimbursed.…”
Section: Challengesmentioning
confidence: 99%
“…This is particularly relevant in light of the fact that most VA medical centers do not have on-site CR programs, necessitating referral to non-VA programs. 7,8 In addition, a qualitative study 25 looking at barriers to CR participation in the VA found that the most common reason for refusal was patient transportation issues. Because there is discussion around expanding community care in the VA alongside the impetus to increase CR participation, our research can help inform both practitioner and patient decisions around referral to CR.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, including those from the physician perspective, have highlighted the importance of their encouragement on CR attendance as well. 13,[25][26][27] Moreover, the center where the study was undertaken is the main cardiac center in the southeast of Iran, so not only local, but nonlocal patients attend this center for treatment. In low-resource settings such as this, it is then important for cardiologists to advocate 28 for regional CR planning, including more capacity so they have spots to which they can refer their patients, as well as alternative models of delivery (eg, home-based, exploiting technology to optimize efficiency and hence increase capacity).…”
Section: Discussionmentioning
confidence: 99%
“…In the qualitative study by Schopfer et al 27 on factors affecting CR attendance, lack of CR information during medical education was one of the barriers identified. This is important as a previous study by Dahhan showed that an increase in physician awareness was associated with increased referral (from 17.6% to 88.96%).…”
Section: Discussionmentioning
confidence: 99%